Evaluasi Produktivitas Bongkar Muat Petikemas pada PT. Berlian Jasa Terminal Indonesia (BJTI Port) di Tanjung Perak-Surabaya - Reny Rochmawati; Ari Widayanti (UM Purwokerto Press, 2021)
Evaluation of loading and unloading productivity is an important thing that must be done because it minimizes the occurrence of obstacles in loading and unloading and helps determine the right steps to increase productivity in the following year. The purpose of this study is to determine the factors that affect the productivity of loading and unloading, calculate the percentage of productivity and determine the forecasting value of loading and unloading productivity for the next 10 years. This is expected to improve services with technological innovation and the development of related science. The method used was the time series method. The results were obtained from PT. BJTI in 2017 – 2020, the obstacles that occurred tended to decrease, so the percentage of productivity increased every year. Based on the forecasting results with the time series method, loading and unloading productivity in 2021 - 2030 showed a significant increase. In 2030 the total productivity of loading and unloading was obtained at 1,397,463 boxes. This showed that the total loading and unloading in 2030 did not affect the equipment's ability in the loading and unloading process because the equipment capacity was still sufficient to accommodate up to 2,242,560 boxes per year. Therefore, it was not necessary to add more HMC tools at Berlian Terminal. This was inversely proportional to the loading and unloading stack obstacles whose solution must be to add RTG heavy equipment so that the loading and unloading process would be faster.